2020
DOI: 10.1007/s12031-020-01490-2
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Molecular Mechanisms of THAP1 Missense Mutations in DYT6 Dystonia

Abstract: Mutations in THAP1 (THAP domain-containing apoptosis-associated protein 1) are responsible for DYT6 dystonia. Until now, more than eighty different mutations in THAP1 gene have been found in patients with primary dystonia, and two third of them are missense mutations. The potential pathogeneses of these missense mutations in human are largely elusive. In the present study, we generated stable transfected human neuronal cell lines expressing wild-type or mutated THAP1 proteins found in DYT6 patients. Transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…This presumption is in line with other studies that show alterations in synaptic transmission due to THAP1 mutations (Zakirova et al, 2018;Frederick et al, 2019;Cheng et al, 2020). In mouse brain, Thap1 mutations or deletions led to impaired synaptic plasticity among other dysregulations in pathways of mitochondrial function and the development of neuronal projections (Zakirova et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This presumption is in line with other studies that show alterations in synaptic transmission due to THAP1 mutations (Zakirova et al, 2018;Frederick et al, 2019;Cheng et al, 2020). In mouse brain, Thap1 mutations or deletions led to impaired synaptic plasticity among other dysregulations in pathways of mitochondrial function and the development of neuronal projections (Zakirova et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…In mouse brain, Thap1 mutations or deletions led to impaired synaptic plasticity among other dysregulations in pathways of mitochondrial function and the development of neuronal projections (Zakirova et al, 2018). Further, THAP1 missense mutations in human neuronal cell models showed dysregulation of target genes related to synaptic function and impaired mitochondrial enzyme activity (Cheng et al, 2020). Phenotypical consequences of a loss-of-function mutation in mice revealed alterations in gene expression of cellular pathways for nervous system development, cytoskeleton, synaptic transmission, and gliogenesis (Frederick et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Other targets of THAP1, like SOD2, were reported by our previous study. 7 However, none of these target genes could link THAP1 mutation to dystonic syndromes. Evidences from ChIP-seq and RNA-seq analysis showed that mouse THAP1 binds to only small part (around 5%) of differentially expressed genes (DEGs) detected in THAP1 -/mouse embryonic stem cells, which may indicate that THAP1 deletion lead to dysregulation of genes mainly through indirect ways, 8 for example through regulation of other key transcription factors.…”
mentioning
confidence: 99%
“…The previous pathway analysis of transcriptome data in animal or overexpressing cell models of THAP1 mutations or knockouts used Gene Ontology (GO) terms or KEGG pathways and implied cytoskeleton, dopamine signaling, eIF2α signaling, mitochondrial dysfunction, neuron projection development, axonal guidance, synaptic long‐term depression, cell adhesion, and inflammatory response in the pathogenesis of DYT‐THAP1 29,32,35,39,44,45 . We also found most of these pathways among the top hits in the GSEA, although pathways are differently named (see Supplementary Table S3).…”
Section: Discussionmentioning
confidence: 89%